OCCURRENCE OF PARASITES IN LIVE Clarias gariepinus SOLD AT JIMETA MODERN MARKET, YOLA, ADAMAWA STATE - Idowu, Thomas A.; James, M.; Sajo, Z. M.; Adedeji, H. A.; Sogbesan, O. A. (FUDMA JOURNAL OF SCIENCES, 2023)
Fish is a cheap and important source of protein and minerals for humans. Clarias gariepinus accounts for over two-thirds of the fish consumed by an average Nigerian family. Various parasites infect C. gariepinus in the wild and in cultured environments, where they are captured and taken to various selling points to be sold to consumers. The present study is aimed at determining the occurrence of parasitic infection in live C. gariepinus from Jimeta Modern Market, Yola, Adamawa State, Nigeria. A total of 30 C. gariepinus were randomly bought from five different fish vendors, six from each. The fish were transported to the Department of Microbiology, Modibbo Adam University, Yola for further studies. The fish sexes were determined before they were examined for parasitic infections. Skin scrapings were obtained, and the gills were examined for ectoparasites while the gastrointestinal tracts were dissected and examined for endoparasites. Parasites were isolated and identified using standard parasitological procedures. Five classes of parasites were identified, namely, Nematode, Trematoda, Protozoa, Cestoda, and Hirudinea. The prevalence of parasites in C. gariepinus sampled from Jimeta Modern Market indicated 57.14% in the male C. gariepinus, while female C. gariepinus were infected with a prevalence rate of 42.85%. This study revealed some major groups of fish parasites that are of zoonotic importance.